Association between transmission modes and chronic Chagas disease clinical forms - Carlos Walmyr de Mattos Oliveira; Luiz Henrique Conde Sangenis; Sergio Salles Xavier; Roberto Magalhães Saraiva; Mauro Felippe Felix Mediano; Andrea Silvestre de Sousa; Alejandro Marcel Hasslocher-Moreno (Revista da Sociedade Brasileira de Medicina Tropical)
ABSTRACT Background: Chagas disease (CD) is associated with significant morbidity and mortality due to cardiac and/or gastrointestinal complications. CD transmission has diverse modes, and their potential relationship with the clinical forms of CD remains unexplored. This study evaluated the association between the transmission modes and chronic clinical forms of CD. Methods: This retrospective study included patients with chronic CD referred to the outpatient clinic of INI/Fiocruz between November 1986 and August 2024. Clinical and epidemiological data were retrieved from medical records. Sociodemographic profiles, epidemiological history of CD, and clinical, cardiac, and digestive evaluations were assessed. Unadjusted and adjusted logistic regression models were fitted to assess the association between transmission modes and CD clinical forms. Results: The analysis included 2,162 patients (53.0% women; mean age 48.3 years). The CD transmission mode was evaluated as vectorial in 1962 (90.8%) patients, followed by blood transfusion in 123 (5.7%), congenital in 59 (2.7%), and oral in 18 (0.8%). Patients with congenital or oral transmission were younger, less likely to be women or self-reported as black, had lower rates of illiteracy, and a higher percentage were from non-endemic areas. No significant associations were observed between transmission modes and the cardiac or digestive forms of CD in unadjusted and adjusted analyses. Conclusions: Vectorial transmission was the most common transmission mode in patients with chronic CD. No significant association was found between the transmission mode and CD clinical forms, indicating that other mechanisms associated with progression to chronic determinate forms should be investigated.